Therapeutic drug monitoring of CT-P13: a comparison of four different immunoassays - Afonso, Joana (2017)
Background: The commercialization of CT-P13, an infliximab (IFX) biosimilar, has the potential to decrease health-related costs and enhance access to biological therapies. This study aimed to address the accuracy and inter-assay agreement of the CT-P13 quantification using four different assays initially developed to assess IFX. Methods: The four different methods, one in-house method and three commercially available kits, were used to quantify exogenously-spiked samples and the sera from 185 inflammatory bowel disease (IBD) patients on CT-P13 therapy. Results: The quantification of the spiked samples unveiled a consistent and accurate behaviour of three of the tested methods, with average percentage recoveries of 90%, 102% and 109%. Results from the clinical samples demonstrated that these three assays were also highly correlated, both concerning Spearman's rank coefficients (range 0.890-0.947) and intraclass correlation coefficients (range 0.907-0.935). There were a few systematic deviations among them, but their impact in the clinical stratification of the patients using different cut-offs was minimal, particularly when these cut-offs were in the 3-4 mu g/ml range, for which the strength of agreement (as assessed by the Kappa statistics that ranged from 0.732 to 0.902) was substantial to almost perfect. Conclusions: Our results indicate that three of the tested IFX quantification methods can be used to accurately quantify CT-P13 without any adjustments.